Menanamkan Etika dengan Membentuk Anak Berkepribadian Melalui Sopan Santun - Debora Purba, Christin; Pirandy, Gusti (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
The author carried out Field Work Practice II at the Department of Social Affairs, Women's Empowerment and Child Protection in Pematang Siantar City. However, the author did a mini project with neighborhood children around the house. The mini project carried out by the author is to shape children's personality through good manners. The problem experienced by the client rather than the author is the lack of good manners in children so that if they are not taught from now on it can have a negative impact on their future growth. From this problem, the author is interested and has the aim of instilling ethics by forming children with personality through good manners, which is a mini project from this author. The author has clients (groups) who experience this problem. Where the group consists of children who are still in elementary school (SD). The author uses social groupwork stages, namely from the preparation stage to the termination stage. The method used is by using a Problem Tree. After carrying out all the stages of social groupwork, the results presented by the author are that clients can instill ethics by forming children with good manners so that children's social skills become more developed and also make it easier for children to interact with other people, and can treat other people with respect.